Uspešno operativno lečenje previđene čiste luksacije Šopartovog zgloba: prikaz dva slučaja i pregled literature - Vasović, Draško; Mičeta, Lazar; Čučaković, Filip; Jevtić, Aleksandar; Jeremić, Danilo; Slavković, Nemanja (Vojnosanitetski pregled, 2025)
Introduction. Chopart joint dislocation (CJD) represents a rare injury that is often initially unrecognized. Because of this, but also because of the increased morbidity it leads to, and due to poor treatment outcomes, this injury represents a significant clinical problem. Case report. We present two patients with overlooked CJD admitted to our institution within one year. The first case was a 63-year-old male, who suffered an injury after falling down the stairs, while the second case was a 33-year-old female injured in a traffic accident. Both patients were initially treated under the diagnosis of foot and ankle sprain. Upon their admission and subsequent computed tomography diagnostics, overlooked pure CJD was diagnosed in both patients. They both underwent open reduction and internal fixation of the Chopart joint using K-wires. Six weeks after the surgery, the K-wires were removed, a below-knee orthosis was applied for walking, and partial weight-bearing was allowed with a gradual increase to full weight-bearing over the next six weeks. Physical therapy was initiated. After the six-month follow-up, both patients were successfully rehabilitated, with a final American Orthopaedic Foot and Ankle Society score of 76 out of 100 for the female patient and a score of 84 out of 100 for the male patient. Conclusion. Despite the delayed diagnosis and postponed operative treatment, the functional outcomes of pure CJD treated by open reduction and percutaneous K-wiring can be satisfactory. Additional studies are required to gain a better insight into the prevalence and causative factors of the possible complications in such a treatment approach to the mentioned injury.